Preparation method and application of photocatalyst CuCo-coated TNS

By growing CuCo layered double hydroxides in situ on the surface of TiO2 nanosheets and calcining under a specific atmosphere, forming a CuCo heterointerface, the stability and reaction conditions of the existing photocatalysts are solved, and the efficient reduction of nitrate to ammonia is achieved.

CN120393981APending Publication Date: 2025-08-01CHONGQING NORMAL UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510522828.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-24
Publication Date
2025-08-01

AI Technical Summary

Technical Problem

Existing photocatalysts have problems such as insufficient stability in degrading nitrate pollution, harsh reaction conditions, low natural light utilization rate and high industrialization difficulty.

Method used

High surface energy TiO2 nanosheets were synthesized by solvothermal method, and CuCo layered double hydroxides were grown on their surface in situ by co-precipitation method, and calcined under a mixed atmosphere of H2/CO2/Ar to form a CuCo heterogeneous interface, optimize the electronic structure and photogenerated carrier separation, and simplify the preparation process.

Benefits of technology

It significantly improves catalytic activity and selectivity, reduces energy consumption and environmental risks, and achieves an efficient process of nitrate reduction to ammonia.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120393981A_ABST
    Figure CN120393981A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a photocatalyst CuCo-coated TNS. The preparation method comprises the following specific steps: step 1, preparing TiO2 (001) nanosheet powder; 2, dissolving copper nitrate and cobalt nitrate in water to obtain a solution A; dispersing the powder prepared in the step 1 in water to obtain a solution B; introducing inert gas into the solution B, and dropwise adding the solution A into the solution B under the protection of inert atmosphere; then, the pH is adjusted to 10; after the reaction is carried out for 5 minutes to 60 minutes, a solid product CuCo coated LDH is collected; and step 3, heating the CuCo-coated LDH prepared in the step 2 to 200-300 DEG C in the atmosphere of H2, CO2 and Ar, calcining for 3-5 hours, and cooling to obtain the photocatalyst CuCo-coated TNS.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of photocatalysis, and particularly relates to a preparation method and application of a photocatalyst CuCo@TNS. Background Art

[0002] The sources of nitrate (NO3 - ) pollution are very extensive, including the excessive use of farm fertilizers, sewage irrigation, industrial wastewater discharge, aquaculture wastewater, and landfill leachate. The natural cycle of nitrogen has been artificially damaged, resulting in an increase in the nitrate content in soil and groundwater. Due to its stable structure, high solubility in water, and fast diffusion, nitrate pollution is extremely likely to occur in surface water. When nitrate enters the human body, it is converted into nitrite under the action of nitrate reductase and forms toxic nitroso compounds in the intestine, which can easily cause food poisoning and other accidents, increase the probability of suffering from blue baby syndrome, and also cause diseases such as cancer, hypertension, and congenital defects. In life, especially the nitrate content in leafy vegetables is relatively high, and overnight meals are likely to convert nitrate into nitrite; when nitrite enters the environmental water body, it is easy to cause eutrophication of the water body, grow a large area of duckweed, etc., resulting in a decrease in dissolved oxygen in the water and a decrease in biodiversity. Therefore, it is necessary to treat nitrate in water bodies.

[0003] In the prior art, the research on photocatalytic degradation of nitrate ions (NO3 - ) mainly focuses on the development of new catalysts and the optimization of reaction mechanisms. For example, the Fe / TiO2 composite material realizes nitrate reduction through the transfer of photo-generated electrons; the g-C3N4-TiO2 heterojunction utilizes visible light response to improve the separation efficiency of electrons and holes and thus improve the nitrate degradation effect; while the oxygen-deficient perovskite-like catalyst (such as A 1-x M x BO 3-y ) enhances the exposure of active sites through lattice regulation; industrial wastes such as titanium-containing blast furnace slag have also been explored for photocatalytic reduction of nitrate. However, these catalysts still have certain problems: (1) Insufficient stability: TiO2-based materials are prone to photocorrosion or surface passivation, resulting in rapid decay of activity; (2) Harsh reaction conditions: Most systems rely on ultraviolet or specific wavelength visible light, and the utilization rate of natural light is low; (3) Difficulty in industrialization: The large-scale preparation process is complex and it is difficult to be actually applied. Summary of the Invention

[0004] Aiming at the above-mentioned deficiencies existing in the prior art, the purpose of the present invention is to provide a preparation method and application of a photocatalyst CuCo@TNS to solve the problems of low degradation rate, low selectivity, dependence on a specific light source, and complex preparation process in the prior art.

[0005] To solve the above technical problems, the present invention adopts the following technical solutions:

[0006] A preparation method of a photocatalyst CuCo@TNS, the specific steps are as follows:

[0007] Step 1: Prepare TiO2(001) nanosheet powder;

[0008] Step 2: Dissolve copper nitrate and cobalt nitrate in water to obtain solution A; Disperse the powder prepared in Step 1 in water to obtain solution B; First, introduce an inert gas into solution B, and then, under the protection of an inert atmosphere, drop solution A into solution B; Subsequently, adjust the pH to 10; After reacting for 5 min to 60 min, collect the solid product CuCo@LDH; Among them, the molar ratio of copper element to cobalt element is (2 - 8):(2 - 8); And the total content of metal ions in the reaction system is 0.1 mol / L; The mass ratio of the total mass of metal elements to the mass of TiO2(001) is (1 - 5):10;

[0009] Step 3: Heat the CuCo@LDH prepared in Step 2 to 200 °C - 300 °C under an atmosphere of H2, CO2 and Ar, calcine for 3 h - 5 h, and cool to obtain the photocatalyst CuCo@TNS.

[0010] Preferably, the synthesis steps of the TiO2(001) nanosheet powder are as follows:

[0011] Slowly drop hydrofluoric acid into tetrabutyl titanate and continuously stir to obtain a mixture; Keep the mixture at a constant temperature of 180 °C - 220 °C for 22 h - 26 h; Collect the solid product and wash it multiple times to obtain TiO2(001) nanosheet powder; Among them, calculated by mass percentage, the concentration of hydrofluoric acid is 35% - 40%; The volume ratio of hydrofluoric acid to tetrabutyl titanate is (1 - 5):25.

[0012] Preferably, in Step 2, the molar ratio of copper element to cobalt element is 5:5.

[0013] Preferably, in Step 2, use a NaOH solution to adjust the pH value, and the concentration of the NaOH solution is 1 mol / L.

[0014] Preferably, in Step 2, the collected solid product is freeze-dried for 12 h - 36 h.

[0015] Preferably, in Step 3, calculated by volume percentage, the volume fraction of H2 in the atmosphere is 40%, the volume fraction of CO2 is 10%, and the volume fraction of Ar is 50%.

[0016] The present invention also provides an application of a photocatalyst CuCo@TNS. The catalyst prepared by the above preparation method catalyzes NO3 in water under light illumination. - to form NH4. + .

[0017] Preferably, the light illumination condition is irradiation by a light source with a wavelength of 190 nm to 2000 nm.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] 1. The present invention uses hydrofluoric acid to regulate the hydrolysis process of tetrabutyl titanate, and synthesizes (001)-faceted TiO2 nanosheets with high surface energy by a solvothermal method. The Ti atoms exposed on this crystal plane have a high coordination unsaturation, which can enhance the separation efficiency of photo-generated carriers and provide a stable carrier structure for subsequent metal loading. At the same time, the (001) plane of the TiO2 nanosheets has a stronger adsorption ability for the intermediate products of the photocatalytic reaction (such as NO3 - ), which can increase the local concentration of reactants and make the reaction proceed in the desired direction.

[0020] 2. The present invention discovers that by in-situ growing a CuCo layered double hydroxide (LDH) on the surface of TiO2 through a coprecipitation method, the synergistic effect of Cu 2 + and Co 2+ optimizes the electronic structure of the active center. Among them, the d-orbital electrons of Co 2+ can promote the capture of the conduction band electrons of TiO2 and inhibit the electron-hole recombination; while Cu 2+ is partially reduced to Cu + during the calcination process to form a Cu + / Cu 2+ redox pair, which accelerates the multi-step hydrogenation process of NO3 - to NH4 + . This bimetallic synergistic mechanism significantly improves the catalytic activity compared with single-metal loading (such as Cu / TiO2 or Co / TiO2).

[0021] 3. The present invention also discovers that during calcination in a H2 / CO2 / Ar mixed atmosphere, H2 selectively reduces Cu-Co LDH to generate metal active sites, while CO2 stabilizes some Co elements through weak oxidation to form a CuCo heterointerface; this interface structure can effectively separate photo-generated carriers and reduce the activation energy of NO3 - reduction through charge redistribution between the two metals, regulate the surface oxygen vacancy concentration of the metal oxide, and enhance the adsorption ability for reaction intermediates.

[0022] 4. The present invention synchronously realizes the synthesis of the TiO2 support and the loading of metal by a one-step solvothermal method, avoiding the multiple calcination steps of the traditional impregnation method; by controlling the pH to promote the formation of the LDH structure, the interlayer anions thereof can serve as proton transfer channels to accelerate the proton-coupled electron transfer (PCET) step during the NO3 - reduction process.

[0023] 5. The present invention uses non-toxic copper nitrate and cobalt nitrate as precursors to replace the toxic metal organic compounds used in the traditional process, and no toxic solvents are required during the preparation process; the mild calcination conditions in the mixed atmosphere further reduce the energy consumption; through the synergistic effects of crystal plane engineering, bimetallic electron regulation, in-situ loading and atmosphere optimization, the present invention realizes a significant improvement in the photocatalytic nitrate reduction activity, while simplifying the process flow and reducing the environmental risk. Brief Description of the Drawings

[0024] Figure 1 It is the synthesis flow chart of the catalyst of the present invention.

[0025] Figure 2 It is the schematic diagram of the photocatalytic reaction test in the present invention.

[0026] Figure 3 It is the catalytic performance diagram of Examples 1-5 and Comparative Examples 8-9.

[0027] Figure 4 It is the catalytic performance comparison diagram of Example 1 and Comparative Examples 6 and 7.

[0028] Figure 5 It is the catalytic performance comparison diagram of Example 1 and Comparative Examples 2, 3 and 4.

[0029] Figure 6 It is the catalytic performance comparison diagram of Example 1 and Comparative Example 1.

[0030] Figure 7 It is the catalytic performance comparison diagram of Example 1 and Comparative Example 5.

[0031] Figure 8 It is the change diagram of the nitrate and ammonium ion concentrations at each time point during the catalytic reaction of Example 1.

[0032] Figure 9 It is the XRD diagram of Examples 1-5 and Comparative Examples 8-9.

[0033] Figure 10 It is the TEM image of TiO2(001) prepared in Example 1.

[0034] Figure 11 It is the TEM image of CuCo@TNS prepared in Example 1. Detailed Embodiments

[0035] The present invention will clearly and completely describe the technical solutions in the embodiments of the present invention in conjunction with the accompanying drawings in the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. All other embodiments obtained by those of ordinary skill in the art based on the present invention belong to the scope of protection of the present invention.

[0036] Unless otherwise specified in specific cases, the numerical ranges listed herein include the upper and lower limit values, as well as all integers and fractions within the range, rather than the specific values listed when defining the range.

[0037] I. A preparation method of a photocatalyst CuCo@TNS

[0038] Step 1: Prepare TiO2(001) nanosheet powder;

[0039] Step 2: Dissolve copper nitrate and cobalt nitrate in water to obtain solution A; disperse the powder prepared in Step 1 in water to obtain solution B; first introduce an inert gas into solution B, and then, under the protection of an inert atmosphere, dropwise add solution A to solution B; subsequently, adjust the pH to 10; after reacting for 5 min to 60 min, collect the solid product CuCo@LDH; wherein, the molar ratio of copper element to cobalt element is (2 - 8):(2 - 8); and the total content of metal ions in the reaction system is 0.1 mol / L; the mass ratio of the total mass of metal elements to the mass of TiO2(001) is (1 - 5):10;

[0040] Step 3: Heat the CuCo@LDH prepared in Step 2 to 200°C to 300°C in an atmosphere of H2, CO2, and Ar, calcine for 3 h to 5 h, and obtain the photocatalyst CuCo@TNS after cooling.

[0041] In some embodiments of the present invention, after in-depth research on the constructed catalytic system, the present invention found that the Cu element plays a leading role in the catalytic system. When the copper content in the catalyst is low, the reaction starts late and does not start to react until after 45 minutes. As the copper content in the catalyst increases, the reaction rate gradually accelerates. When the copper to cobalt molar ratio is 5:5, the catalytic performance reaches the best. However, as the copper content is further improved, its catalytic effect is not as good as the catalyst containing only copper. This is because as the copper content is further improved, the adverse effects of the cobalt element are further amplified, resulting in a decline in catalytic performance. Although not as good as the catalytic system of a single copper element, it is still better than the catalytic system of a single cobalt element. Therefore, the molar ratio of copper to cobalt can be 2:8, 4:6, 5:5, 6:4, 8:2, etc., as well as all ranges and sub-ranges between the above values. It should be understood that in embodiments, any of the above ranges can be combined with any other ranges in other embodiments.

[0042] In some embodiments of the present invention, the synthesis steps of the TiO2(001) nanosheet powder are as follows:

[0043] Slowly add hydrofluoric acid dropwise to tetrabutyl titanate and continue stirring to obtain a mixture; the mixture is reacted at a constant temperature of 180°C to 220°C for 22h to 26h; the solid product is collected and washed several times to obtain TiO2 (001) nanosheet powder; wherein, the concentration of hydrofluoric acid is 35% to 40% by mass percentage; the volume ratio of hydrofluoric acid to tetrabutyl titanate is (1 to 5): 25. The present invention uses hydrofluoric acid to regulate the hydrolysis process of tetrabutyl titanate to prepare TiO2 nanosheets with exposed (001) crystal planes. By comparing TiO2 (001) and TiO2 (101) catalysts loaded with the same metal ratio and calcined at the same temperature, the Ti atom coordination unsaturation of the TiO2 (001) crystal plane prepared by the present invention is high, which enhances the efficiency of photogenerated carrier separation; at the same time, it has a great impact on NO3 - The adsorption capacity of intermediate products is significantly better than that of the (101) crystal plane, making the catalytic effect of TiO2 (001) supported catalyst better.

[0044] In some embodiments of the present invention, the mass ratio of the total mass of the metal elements to the mass of TiO2(001) is between (1-5):10. The mass ratio of the total mass of the metal elements to the mass of TiO2(001) is further preferably 1:10. It should be understood that in embodiments, any of the above ranges can be combined with any other ranges in other embodiments.

[0045] In some embodiments of the present invention, in step 2, a NaOH solution is used to adjust the pH value, and the concentration of the NaOH solution is 1 mol / L.

[0046] In some embodiments of the present invention, in step 2, the collected solid product is freeze-dried for 12 h to 36 h.

[0047] In some embodiments of the present invention, in step 3, calculated by volume percentage, the volume ratio of H2 in the atmosphere is 40%, the volume ratio of CO2 is 10%, and the volume ratio of Ar is 50%.

[0048] II. Application of a photocatalyst CuCo@TNS

[0049] The catalyst prepared by the preparation method of the present invention catalyzes NO3 in water under light irradiation - to form NH4 + . Among them, the light irradiation condition is light irradiation by a light source with a wavelength of 190 nm to 2000 nm. For example, a xenon lamp can be used as the light source for photocatalytic reaction.

[0050] III. Examples and comparative examples

[0051] Example 1

[0052] Step 1: Synthesis of TiO2(001) nanosheets: Under magnetic stirring, 3.0 mL of HF (37%) solution was slowly dropped into 25 mL of tetrabutyl titanate and mixed well to form a homogeneous solution, and continuously stirred for 2 h. Then the mixture was transferred to a 50 mL polytetrafluoroethylene autoclave and kept at 200 °C for 24 h. After hydrothermal synthesis, the solid product was centrifuged at 7000 rpm for 1 minute in a centrifuge, the precipitate was collected, and washed repeatedly with water and ethanol (3 times each, and the last time with ethanol). The sample was further dispersed in an aqueous solution of NaOH (0.1 mol / L), stirred for 24 h, centrifuged at 7000 rpm for 1 minute to recover the solid powder, washed with water until neutral, and dried at 60 °C to obtain TiO2(001) nanosheets, denoted as TNS.

[0053] Step 2: In-situ preparation of TiO2 photocatalyst supported by Cu-Co ultrathin hydrotalcite (LDH): Take 0.058615 g of anhydrous copper nitrate (Cu(NO3)2) and 0.090945 g of cobalt nitrate hexahydrate (Co(NO3)2·6H2O), ultrasonic and stir to dissolve them in 25 mL of deionized water to obtain a metal ion solution. Then take 0.382805 g of the synthesized TiO2(001) powder and ultrasonic disperse it in 50 mL of deionized water to form a homogeneous solution. First, transfer the TiO2(001) suspension to a three-necked flask, pre-wash it with Ar gas for 15 minutes, and under the protection of Ar gas (100 ml per minute), drop the metal ion solution into the TiO2(001) suspension. Subsequently, slowly drop the NaOH solution (the concentration of the NaOH solution is 1 mol / L) into the solution, use a pH meter to detect the pH of the TiO2(001) suspension in real time, and continuously drop the NaOH solution to adjust the pH to 10. After reacting for 30 minutes, centrifuge at 7000 rpm for 1 minute to collect the solid product, and freeze-dry it for 24 hours to obtain the TiO2 photocatalyst supported by Cu-Co ultrathin hydrotalcite, denoted as CuCo@LDH.

[0054] Step 3: Preparation of TiO2 photocatalyst supported by Cu-Co nanoalloy: Calcinate the TiO2 photocatalyst supported by Cu-Co ultrathin hydrotalcite (LDH) prepared in Step 2 at 250 °C for 4 hours (heating rate is 2 °C per minute) under the atmosphere of 40% H2, 10% CO2, and 50% Ar, and collect the TiO2 photocatalyst supported by Cu-Co nanoalloy denoted as CuCo@TNS after natural cooling.

[0055] Example 2

[0056] Based on Example 1 with adjustments, the difference is that the molar ratio of copper ions to cobalt ions is 2:8. Specifically, the masses of anhydrous copper nitrate (Cu(NO3)2) and cobalt nitrate hexahydrate (Co(NO3)2·6H2O) are 0.023445 g and 0.145515 g, and the mass of the TiO2(001) powder is 0.37412 g. Other steps are exactly the same as those in Example 1.

[0057] Example 3

[0058] Based on Example 1 with adjustments, the difference is that the molar ratio of copper ions to cobalt ions is 4:6. Specifically, the masses of anhydrous copper nitrate (Cu(NO3)2) and cobalt nitrate hexahydrate (Co(NO3)2·6H2O) are 0.04689 g and 0.109135 g, and the mass of the TiO2(001) powder is 0.37991 g. Other steps are exactly the same as those in Example 1.

[0059] Example 4

[0060] Based on Example 1 with adjustments, the difference lies in that: the molar ratio of copper ions to cobalt ions is 6:4. Specifically, the masses of anhydrous copper nitrate (Cu(NO3)2) and cobalt nitrate hexahydrate (Co(NO3)2·6H2O) are 0.070335 g and 0.07276 g, and the mass of TiO2(001) powder is 0.3857 g. Other steps are exactly the same as those in Example 1.

[0061] Example 5

[0062] Based on Example 1 with adjustments, the difference lies in that: the molar ratio of copper ions to cobalt ions is 8:2. Specifically, the masses of anhydrous copper nitrate (Cu(NO3)2) and cobalt nitrate hexahydrate (Co(NO3)2·6H2O) are 0.09378 g and 0.03638 g, and the mass of TiO2(001) powder is 0.391475 g. Other steps are exactly the same as those in Example 1.

[0063] Comparative Example 1

[0064] Based on Example 1 with adjustments, the difference lies in that: in Step 2, TiO2(001) is not added, and Cu-Co ultrathin hydrotalcite (LDH) is first prepared; then, according to Step 3 of Example 1, the Cu-Co ultrathin hydrotalcite (LDH) is calcined to obtain CuCo alloy powder; then, the CuCo alloy and TiO2(001) are heterogeneously loaded. The specific steps are as follows:

[0065] Take the CuCo alloy powder and disperse it in 25 ml of deionized water to form suspension a, and then take the TiO2(001) powder and disperse it in 25 ml of deionized water to form suspension b, ensuring that the molar ratio of Cu, Co, and TiO2 in this comparative example is exactly the same as that in Example 1. Under ultrasonic conditions, slowly drop suspension a into suspension b. After all of suspension a is dropped into suspension b, continue to maintain ultrasonic for half an hour. Subsequently, collect the mixed suspension, centrifuge it at 7000 rpm for 1 minute to recover the solid powder, wash it 3 times with deionized water, and then freeze-dry it for 24 hours to obtain the TiO2 photocatalyst with heterogeneously loaded Cu-Co alloy.

[0066] Other steps in this comparative example are exactly the same as those in Example 1.

[0067] Comparative Example 2

[0068] Based on Example 1 with adjustments, the difference lies in that: Co is replaced by Fe. Other steps are exactly the same as those in Example 1, and an FeCu catalyst is prepared.

[0069] Comparative Example 3

[0070] Based on Example 1, the adjustment is as follows: Cu is replaced by Fe. Other steps are exactly the same as those in Example 1, and an FeCo catalyst is prepared.

[0071] Comparative Example 4

[0072] Based on Example 1, the adjustment is as follows: Fe is added. Other steps are exactly the same as those in Example 1, and an FeCoCu catalyst is prepared.

[0073] Comparative Example 5

[0074] Based on Example 1, the adjustment is as follows: The preparation method of TiO2 is different from that in Example 1. The solvothermal method is adopted, and the specific steps are as follows:

[0075] Under magnetic stirring, 3.0 mL of deionized water solution was slowly dropped into 25 mL of tetrabutyl titanate and mixed thoroughly to form a homogeneous solution, and continuously stirred for 2 h. Then the mixture was transferred to a 50 mL polytetrafluoroethylene autoclave and kept at 200 °C for 24 h. After hydrothermal synthesis, the solid product was centrifuged at 7000 rpm for 1 minute in a centrifuge, the precipitate was collected, and washed repeatedly with water and ethanol (3 times each, and the last time with ethanol). The sample was further dispersed in an aqueous solution of NaOH (0.1 mol / L), stirred for 24 h, centrifuged at 7000 rpm for 1 minute to recover the solid powder, washed with water until neutral, and dried at 60 °C to obtain TiO2(101) nanosheets. Other steps are exactly the same as those in Example 1, and TiO2(101) nanosheets are used to replace TiO2(001) nanosheets in Example 1.

[0076] Comparative Example 6

[0077] Based on Example 1, the adjustment is as follows: The calcination temperature in Step 3 is 350 °C. Other steps are exactly the same as those in Example 1.

[0078] Comparative Example 7

[0079] Based on Example 1, the adjustment is as follows: Calcination is not carried out in Step 3, that is, CuCo@LDH is directly used for the catalytic reaction. Other steps are exactly the same as those in Example 1.

[0080] Comparative Example 8

[0081] Based on Example 1, the adjustment is made. The difference lies in that the molar ratio of copper ions to cobalt ions is 0:10. Specifically, the masses of anhydrous copper nitrate (Cu(NO3)2) and cobalt nitrate hexahydrate (Co(NO3)2·6H2O) are 0 g and 0.181893 g, and the mass of TiO2(001) powder is 0.36833 g. Other steps are exactly the same as those in Example 1.

[0082] Comparative Example 9

[0083] Based on Example 1, the adjustment is made. The difference lies in that the molar ratio of copper ions to cobalt ions is 10:0. Specifically, the masses of anhydrous copper nitrate (Cu(NO3)2) and cobalt nitrate hexahydrate (Co(NO3)2·6H2O) are 0.117225 g and 0 g, and the mass of TiO2(001) powder is 0.397275 g. Other steps are exactly the same as those in Example 1.

[0084] IV. Performance Comparison

[0085] Using the self-made photocatalytic reactor as Figure 2 shown, the photocatalysts prepared in the examples and comparative examples were used to conduct the performance detection of catalyzing NO3 - to NH4 + . Among them, the initial concentration of NO3 - in the solution was 10 ppm. The solution at different reaction times was detected by ion chromatography, and the NH4 + concentrations at each time point are shown in Table 1 below.

[0086] Table 1 (measurement unit: ppm)

[0087]

[0088] Finally, it should be noted that the above examples are only used to illustrate the technical solutions of the present invention rather than to limit the technical solutions. Those of ordinary skill in the art should understand that any modifications or equivalent replacements made to the technical solutions of the present invention without departing from the purpose and scope of the present technical solution should be covered within the scope of the claims of the present invention.

Claims

1. A preparation method of a photocatalyst CuCo@TNS, characterized in that, The specific steps are as follows: Step 1: Prepare TiO2(001) nanosheet powder; Step 2: Dissolve copper nitrate and cobalt nitrate in water to obtain solution A; Disperse the powder prepared in Step 1 in water to obtain solution B; First, introduce an inert gas into solution B, and then, under the protection of an inert atmosphere, dropwise add solution A to solution B; Subsequently, adjust the pH to 10; After reacting for 5 min to 60 min, collect the solid product CuCo@LDH; Among them, the molar ratio of copper element to cobalt element is (2 - 8):(2 - 8); and the total content of metal ions in the reaction system is 0.1 mol / L; The mass ratio of the total mass of metal elements to the mass of TiO2(001) is (1 - 5):10; Step 3: Heat the CuCo@LDH prepared in Step 2 to 200 °C - 300 °C in an atmosphere of H2, CO2 and Ar, calcine for 3 h - 5 h, and after cooling, obtain the photocatalyst CuCo@TNS.

2. The preparation method according to claim 1, wherein The synthesis steps of the TiO2(001) nanosheet powder are as follows: Slowly drop hydrofluoric acid into tetrabutyl titanate and continuously stir to obtain a mixture; Keep the mixture reacting at a constant temperature of 180 °C - 220 °C for 22 h - 26 h; Collect the solid product and wash it many times to obtain TiO2(001) nanosheet powder; Among them, calculated by mass percentage, the concentration of hydrofluoric acid is 35% - 40%; The volume ratio of hydrofluoric acid to tetrabutyl titanate is (1 - 5):

25.

3. The preparation method according to claim 1, wherein In Step 2, use a NaOH solution to adjust the pH value, and the concentration of the NaOH solution is 1 mol / L.

4. The preparation method according to claim 1, wherein In Step 2, freeze-dry the collected solid product for 12 h - 36 h.

5. The preparation method according to claim 1, characterized in that, In Step 3, calculated by volume percentage, the volume fraction of H2 in the atmosphere is 40%, the volume fraction of CO2 is 10%, and the volume fraction of Ar is 50%.

6. Application of a photocatalyst CuCo@TNS, characterized in that, The catalyst prepared by the preparation method according to any one of claims 1 to 5 catalyzes NO3 in water under light conditions - to form NH4 + .

7. The application according to claim 6, characterized in that The light condition is irradiation by a light source with a wavelength of 190 nm - 2000 nm.